PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN, DAN COPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT - Fadhila Adhipradana; Daljono Daljono (Diponegoro Journal of Accounting, 2014)
This study aims to determine the effect of financial performance, firm size, and corporate governance on the disclosure of sustainability report arranged by companies listed on the Indonesia Stock Exchange. This study is a replication of previous research, by adding new variables. The Independent variables used in this study are profitability, liquidity, dividend payment ratio, total assets, total employees, the audit committee, the board of commissioners, committee governance, management ownership, and foreign ownership. The dependent variable used is the disclosure of sustainability report. The samples are companies listed on the Indonesia Stock Exchange (BEI) that disclose the Sustainability Report with 2008-2011 of study period. The samples used are 50 companies; 25 companies with the sustainability report revealed and 25 without the sustainability report revealed. The data of companies without the sustainability revealed is collected by stratified random sampling method. This study uses t-test and logistic regression for data analysis. The result of the test is that the total assets, total employees, and governance committee positive influence to the disclosure of Sustainability Report. Meanwhile, the variable of profitability, liquidity, dividend payout ratio, audit committee, board of commissioners, management ownership, and foreign ownership has not influence on the disclosure of Sustainability Report.